2005
DOI: 10.1128/aac.49.7.2606-2611.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Actions of the Two Component Peptides of the Lantibiotic Lacticin 3147 Explain Its Antimicrobial Activity at Nanomolar Concentrations

Abstract: Lacticin 3147 is a two-peptide (LtnA1 and LtnA2) lantibiotic produced by Lactococcus lactis subsp. lactis DPC3147 and has inhibitory activity against all gram-positive microorganisms tested. In this study the specific activities of the component peptides (alone or in combination) were determined by using L. lactis subsp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 33 publications
8
83
1
Order By: Relevance
“…In this way, the following pORI280-ltnA1A2 derivatives were made: pOri-ltnA1S7T (primer pair [21][22], pOri-ltnA1S7G (primer pair 24-25), pOri-ltnA1S7V (primer pair 27-28), pOri-ltnA2S9T (primer pair 30-31), pOri-ltnA2S9G (primer pair 33-34), pOri-ltnA2S9V (primer pair 36-37), pOriltnA2S9,12T (primer pair 39-40), pOri-ltnA2S9,12G (primer pair 42-43), and pOri-ltnA2S9,12V (primer pair 45-46). Screening of candidate EC101 transformants was facilitated by the use of check primers 23,26,29,32,35,38,41,44, and 47, respectively, in conjunction with either primer 7 or 8, depending on the orientation of the check primer. In all cases successful mutagenesis was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the following pORI280-ltnA1A2 derivatives were made: pOri-ltnA1S7T (primer pair [21][22], pOri-ltnA1S7G (primer pair 24-25), pOri-ltnA1S7V (primer pair 27-28), pOri-ltnA2S9T (primer pair 30-31), pOri-ltnA2S9G (primer pair 33-34), pOri-ltnA2S9V (primer pair 36-37), pOriltnA2S9,12T (primer pair 39-40), pOri-ltnA2S9,12G (primer pair 42-43), and pOri-ltnA2S9,12V (primer pair 45-46). Screening of candidate EC101 transformants was facilitated by the use of check primers 23,26,29,32,35,38,41,44, and 47, respectively, in conjunction with either primer 7 or 8, depending on the orientation of the check primer. In all cases successful mutagenesis was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…This result is almost certainly caused by the isolation procedure, which relies on desorption of the peptides, presumably from a receptor͞ immunity protein on the surface of the producer cell. Indeed, we have previously shown that binding to target cells is a two-step process mediated by LtnA1 (32). Consequently, in the absence of LtnA1, LtnA2 is likely to be lost in the supernatant because it has no receptor peptide to facilitate binding.…”
Section: Identification Of a Dha Reductase Ltnj Responsible For The Smentioning
confidence: 99%
“…A recent study on the mode of action of lacticin 3147 demonstrated that Ltn␣ binds to the peptidoglycan precursor lipid II (12), a result that was anticipated because of the structural similarity between Ltn␣ and mersacidin, which also binds to lipid II (13). However, in order for lacticin 3147 to inhibit cell wall biosynthesis and form small pores in the cell membrane, Ltn␤ is also necessary, leading to a proposed model in which the lipid II:Ltn␣ complex recruits Ltn␤ to form an active complex (12,14).…”
mentioning
confidence: 99%
“…This understanding could be used to develop novel lantibiotics based on designing peptide sequences that can be site-specifically modified to yield new products. Given the synergy observed among twocomponent lantibiotics, which display similar or higher activity than the best single-component lantibiotic nisin (14), the possibility of engineering new lantibiotics with therapeutic potential is even greater for these systems.…”
mentioning
confidence: 99%
“…The 2-component lantibiotics (lanthionine and methyllanthionine) are small microbial peptide bacteriocins produced by Gram positive bacteria such as Lactococcus lactis (Lawton et al, 2007). At nanomolar concentration, these peptides actively inhibit multidrug resistant pathogens by targeting the lipid II component of the bacterial cell wall (Morgan et al, 2005). Lactobacilli are also known to produce non-lanthione containing bacteriocins.…”
Section: Production Of Inhibitory Substancesmentioning
confidence: 99%